2022
DOI: 10.1038/s41467-022-32579-4
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the mitotic machinery to drive cellular elongation and chromatin reorganisation in Plasmodium falciparum gametocytes

Abstract: The sexual stage gametocytes of the malaria parasite, Plasmodium falciparum, adopt a falciform (crescent) shape driven by the assembly of a network of microtubules anchored to a cisternal inner membrane complex (IMC). Using 3D electron microscopy, we show that a non-mitotic microtubule organizing center (MTOC), embedded in the parasite’s nuclear membrane, orients the endoplasmic reticulum and the nascent IMC and seeds cytoplasmic microtubules. A bundle of microtubules extends into the nuclear lumen, elongating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 62 publications
9
51
1
Order By: Relevance
“…EBs are evolutionarily conserved in eukaryotes from yeast to human [27][28][29][30]. In the Plasmodium, EB1 is the only member of this family and it showed a nuclear localization when episomally expressed in the P. falciparum [31], suggesting a role related to the spindle. However, it remains unclear for the precise localization and function of EB1 in the Plasmodium life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…EBs are evolutionarily conserved in eukaryotes from yeast to human [27][28][29][30]. In the Plasmodium, EB1 is the only member of this family and it showed a nuclear localization when episomally expressed in the P. falciparum [31], suggesting a role related to the spindle. However, it remains unclear for the precise localization and function of EB1 in the Plasmodium life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…S4). We detected Pf SPB at the parasite’s centrosome, also called centriolar plaque, which organizes intranuclear microtubules (Li et al, 2022; Rashpa and Brochet, 2022; Simon et al, 2021). At the centriolar plaque, Pf SPB localized between the extranuclear centrin and the intranuclear tubulin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SPMTs of P. falciparum are extremely stable exemplified by their resistance to classic microtubule depolymerizing agents (16). Recent studies showed polyglutamylation of SPMTs in merozoites (17) and gametocytes (13) and suggested its involvement in SPMT stability (17). A second population of microtubules, the spindle microtubules, is necessary to coordinate chromosome segregation and these extend from a single MTOC throughout the nucleus (14, 18).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to invasive stages such as sporozoites, merozoites and ookinetes, gametocytes lack apical polarity and an apical polar ring from which SPMTs emanate. A recent study reports the nucleation of SPMTs in gametocytes at the outer centriolar plaque, a non-mitotic MTOC embedded in the nuclear membrane of the parasite (13). The SPMT network disassembles in stage V gametocytes, providing an increased deformability that is expected to permit transmigration across the endothelial barrier and exit from the bone marrow (27, 28).…”
Section: Introductionmentioning
confidence: 99%